defpred S1[ object , object ] means for h being Morphism of C st h = \$1 holds
\$2 = (g (*) h) (*) f;
set X = Hom ((cod f),(dom g));
set Y = Hom ((dom f),(cod g));
A1: for x being object st x in Hom ((cod f),(dom g)) holds
ex y being object st
( y in Hom ((dom f),(cod g)) & S1[x,y] )
proof
let x be object ; :: thesis: ( x in Hom ((cod f),(dom g)) implies ex y being object st
( y in Hom ((dom f),(cod g)) & S1[x,y] ) )

A2: ( Hom ((dom f),(cod f)) <> {} & f is Morphism of dom f, cod f ) by ;
assume A3: x in Hom ((cod f),(dom g)) ; :: thesis: ex y being object st
( y in Hom ((dom f),(cod g)) & S1[x,y] )

then reconsider h = x as Morphism of cod f, dom g by CAT_1:def 5;
take (g (*) h) (*) f ; :: thesis: ( (g (*) h) (*) f in Hom ((dom f),(cod g)) & S1[x,(g (*) h) (*) f] )
( Hom ((dom g),(cod g)) <> {} & g is Morphism of dom g, cod g ) by ;
then A4: g (*) h in Hom ((cod f),(cod g)) by ;
then g (*) h is Morphism of cod f, cod g by CAT_1:def 5;
hence ( (g (*) h) (*) f in Hom ((dom f),(cod g)) & S1[x,(g (*) h) (*) f] ) by ; :: thesis: verum
end;
consider h being Function such that
A5: ( dom h = Hom ((cod f),(dom g)) & rng h c= Hom ((dom f),(cod g)) ) and
A6: for x being object st x in Hom ((cod f),(dom g)) holds
S1[x,h . x] from ( Hom ((dom f),(cod g)) = {} implies Hom ((cod f),(dom g)) = {} ) by Th50;
then reconsider h = h as Function of (Hom ((cod f),(dom g))),(Hom ((dom f),(cod g))) by ;
take h ; :: thesis: for h being Morphism of C st h in Hom ((cod f),(dom g)) holds
h . h = (g (*) h) (*) f

thus for h being Morphism of C st h in Hom ((cod f),(dom g)) holds
h . h = (g (*) h) (*) f by A6; :: thesis: verum